GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG PERUBAHAN FISIOLOGIS PADA KEHAMILAN DI PUSKESMAS KUTASARI KECAMATAN KUTASARI KABUPATEN PURBALINGGA TAHUN 2008 - Dita Maryanta; Arlyana Hikmanti (Universitas Harapan Bangsa Purwokerto, 2009)
Background : The physical changes that occur during pregnancy, will affect the sense ofcomfort during the pregnancy. Ignorance pregnant women about the physical changes thatoccur, may lead to a false perception of the mother. Perception that one will be taken the wrongresponse anyway. Hopefully with the handling of disease symptoms during pregnancy that canquickly reduce the risk of maternal death from complications of pregnancy. Objective : This study aims to describe the level of knowledge of pregnant women about thephysiological changes in pregnancy in Kutasari Health Center in 2008. Methods : This study is a quantitative descriptive study with cross sectional approach. Samplingtechnique in this study used purposive sampling, samples of this study were all pregnant womenin health centers Kutasari in 2012 by 93 respondents. Instrument used questionnaires and typesof data are primary data. Analysis of the data using univariate analysis. Results : Most of the knowledge of pregnant women about the physiological changes inpregnancy is enough (63.4%), respondents with age < 20, 20-35 years and >35 years old haveenough knowledge. Respondents with elementary and high school education have sufficientknowledge level, junior high school has less knowledge levels and university education (PT) hasa good level of knowledge. Respondents with electronic media resources, mass media and healthworkers have sufficient knowledge. Respondents with IRT work, farmers and the private sectorhas sufficient knowledge and respondents with jobs most civil servants have good knowledge. Keywords : Knowledge Level, Age, Education, Resources, Jobs